Temperature-sensitive liposomal ciprofloxacin for the treatment of biofilm on infected metal implants using alternating magnetic fields. (17th February 2018) - Munaweera, Imalka; Shaikh, Sumbul; Maples, Danny; Nigatu, Adane S.; Sethuraman, Sri Nandhini; Ranjan, Ashish; Greenberg, David E.; Chopra, Rajiv
Abstract: Implants are commonly used as a replacement for damaged tissue. Many implants, such as pacemakers, chronic electrode implants, bone screws, and prosthetic joints, are made of or contain metal. Infections are one of the difficult to treat complications associated with metal implants due to the formation of biofilm, a thick aggregate of extracellular polymeric substances (EPS) produced by the bacteria. In this study, we treated a metal prosthesis infection model using a combination of ciprofloxacin-loaded temperature-sensitive liposomes (TSL) and alternating magnetic fields (AMF). AMF heating is used to disrupt the biofilm and release the ciprofloxacin-loaded TSL. The three main objectives of this study were to (1) investigate low- and high-temperature-sensitive liposomes (LTSLs and HTSLs) containing the antimicrobial agent ciprofloxacin for temperature-mediated antibiotic release, (2) characterise in vitro ciprofloxacin release and stability and (3) study the efficacy of combining liposomal ciprofloxacin with AMF against Pseudomonas aeruginosa biofilms grown on metal washers. The release of ciprofloxacin from LTSL and HTSL was assessed in physiological buffers. Results demonstrated a lower transition temperature for both LTSL and HTSL formulations when incubated in serum as compared with PBS, with a more pronounced impact on the HTSLs. Upon combining AMF with temperature-sensitive liposomal ciprofloxacin, a 3 log reduction in CFU of Pseudomonas aeruginosa in biofilm was observed. Our initial studies suggest that AMF exposure on metal implants can trigger release of antibiotic from temperature sensitive liposomes for a potent bactericidal effect on biofilm.